Kinetics and mechanism of low‐concentration CO2 adsorption on solid amine in a humid confined space. (26th July 2018) - Si, Wenting; Ye, Sha; Zhang, Dongxiao; Yang, Bin; Hou, Yang; Li, Zhongjian; Zhang, Xingwang; Zhu, Jingke; Lei, Lecheng
Abstract: The kinetics and mechanism of low‐concentration CO2 adsorption on a solid‐supported polyethylenimine (PEI) adsorbent in a humid confined space were investigated, where the content of CO2 was about 0.4 % (v). A flow system, equipped with a dew point meter and IR gas analyzer connected in series for online measurement, was developed and the co‐adsorption performance of CO2 and H2 O was analyzed. It was found that the H2 O adsorption capacity and activation energy were not significantly changed when 0.4 % (v) CO2 was applied in the co‐adsorption process, indicating that the effect of dilute CO2 could be neglected. However, the CO2 adsorption capacity increased with the assistance of H2 O, and then it decreased slightly when the H2 O content in air flow was above 1.56 % (v). This implied that the adsorption activation energy of CO2 could be significantly reduced due to the existence of H2 O in air flow. The direct formation of bicarbonate on the supported PEI adsorbent was favoured for the co‐adsorption process of CO2 and H2 O.